2021
DOI: 10.3390/ijms222111550
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy Strategy for Alzheimer’s and Parkinson’s Diseases Aimed at Preventing the Formation of Neurotoxic Oligomers in SH-SY5Y Cells

Abstract: We present here a gene therapy approach aimed at preventing the formation of Ca2+-permeable amyloid pore oligomers that are considered as the most neurotoxic structures in both Alzheimer’s and Parkinson’s diseases. Our study is based on the design of a small peptide inhibitor (AmyP53) that combines the ganglioside recognition properties of the β-amyloid peptide (Aβ, Alzheimer) and α-synuclein (α-syn, Parkinson). As gangliosides mediate the initial binding step of these amyloid proteins to lipid rafts of the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…However, it excludes common post-translational modifications of proteins, such as phosphorylation, glycosylation or lipidation, that can be predicted from consensus amino acid motifs [ 3 ]. Membrane proteins are a perfect example of this paradigm, as specific lipids act as key cofactors (i.e., chaperones) for protein folding and stability [ 27 , 38 , 39 , 40 , 41 , 42 ]. The existence of protein-lipid “co-structures” have been identified as an issue for the heterologous expression of membrane proteins [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it excludes common post-translational modifications of proteins, such as phosphorylation, glycosylation or lipidation, that can be predicted from consensus amino acid motifs [ 3 ]. Membrane proteins are a perfect example of this paradigm, as specific lipids act as key cofactors (i.e., chaperones) for protein folding and stability [ 27 , 38 , 39 , 40 , 41 , 42 ]. The existence of protein-lipid “co-structures” have been identified as an issue for the heterologous expression of membrane proteins [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such pores can allow a catastrophic and irreversible entry of calcium ions [87]. This has led to the construction of a small peptide inhibitor that recognizes the gangliosides that are implicated in the initial binding step of amyloid proteins to the lipid rafts of the cell membranes, thereby blocking the neurodegeneration-provoking calcium influx [88,89].…”
Section: Other Interactionsmentioning
confidence: 99%
“…Among such oligomers, those forming pores in the plasma membrane of brain cells exhibit the highest toxicity since such species favor the penetration of Ca 2+ ions in massive amounts. The investigation of GG involvement in the toxicity of these oligomers has recently confirmed that gangliosides are relevant therapeutic targets for both AD and PD [ 82 ]. On the other hand, the ability of GM1 to protect against α-synuclein toxicity in vivo has also been postulated.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%